(untitled) (Research, Society and Development, 2023)
Aging causes functional decline, in addition to greater physical and cognitive restrictions that make the elderly more vulnerable and dependent on other people’s care. This group is also more likely to develop oral diseases when compared to other age groups, and with the growth of the country’s elderly population, home dental care becomes increasingly necessary. Through a bibliographical review using scientific articles and official documents available in full on Google Scholar, Pubmed and the Virtual Health Library on home care for the elderly, it was possible to explore the essentiality of the dentist as a component of the multidisciplinary health team in dental care home for the elderly. The literature presents the main problems as dental caries, including root cavities, periodontal diseases, and the presence of various oral lesions. Also noteworthy are the adaptations that dental surgeons must make to machinery, instrumentation, and biosafety at a distance from a clinical environment. It is concluded that dentistry professionals have a lot to contribute to the quality of life of the elderly through specialized care adapted to the reality of domiciled patients.